2012 IEEE International Conference on Communications (ICC) 2012
DOI: 10.1109/icc.2012.6364747
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an energy-efficient radio architecture for opportunistic communication

Abstract: Abstract-A major challenge for wireless networks is to minimize the energy consumption in the mobile devices. This work evaluates potential performance gains of a dual-radio architecture in which a low power radio is used to wake up the primary high power radio. Our targeted domain is opportunistic communication directly between devices. We show that it can significantly reduce the energy consumption at a price of slightly decreased goodput. We also examine the effect of the MAC protocol on the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This is due to the characteristics of the low-power 802.15.4 radio which is unable to perform the node and service discovery in areas with high density. (For more explanation see [7].) However, in Fig.…”
Section: B Infinite Batterymentioning
confidence: 97%
See 3 more Smart Citations
“…This is due to the characteristics of the low-power 802.15.4 radio which is unable to perform the node and service discovery in areas with high density. (For more explanation see [7].) However, in Fig.…”
Section: B Infinite Batterymentioning
confidence: 97%
“…Such dual-radio architectures only wake up the high-power radio when a useful contact has been found. We have also investigated this possibility in a previous work [7], and the results showed that it may prolong the battery lifetime of nodes in opportunistic network. However, since a secondary radio is often not available on personal mobile devices, the applicability is limited.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations